Managerial Competence of a School Principal in Managing School Facilities and Infrastructure: A Case of SD Negeri 2 Trienggadeng - Julianti, Julianti; Yusrizal, Yusrizal; Niswanto, Niswanto (FKIP Universitas Lampung, 2021)
The aim of this research was to identify how the school facilities and infrastructure of State Elementary School 2 of Trienggadeng in Pidie Jaya Regency were planned, utilized, and maintained. A descriptive method with a qualitative approach was used in this research. The data were collected by doing observation, interview, and documentation. The subjects of this research were the school principal, the school committee, the school facilities and infrastructure manager, and the teachers of State Elementary School 2 of Trienggadeng. The results indicate that the plan related to the management of the school facilities and infrastructure was made by the principal by involving the school committee, the school facilities and infrastructure manager, and the teachers. Moreover, as a manager as well as an administrator, the principal also (a) made the plan carefully by considering many aspects, (b) socialized and monitored the execution of the plan, (c) organized the maintenance of the facilities and infrastructure, and (d) monitored the management of the facilities and infrastructure.Keywords: managerial competence, school principal, qualitative research.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202105